HOMOSEXUAL CRIME TOWARDS CHILDREN IN BENGKULU PROVINCE VIEWED FROM ISLAMIC LAW PERSPECTIVE - Muhammad Bayu Masifa Asbei; Muhammad Darudin; Sirman Dahwal (Universitas Bengkulu, 2020)
Homosexual crime behavior on children in Bengkulu province experiences increase every year. Viewed from various religions officially recognized by the state, homosexual behavior categorized as acts that are in contrast to religious values, and Islam condemns such acts. From this background, the problems to be investigated can be formulated as follow: (1) what were the factors causing the occurrence of homosexual crimes on children in Bengkulu province?; (2) what were the criminal sanctions that can be imposed on the subjects of homosexual crimes against children in terms of Islamic law?. To answer these problems, it was used empirical juridical research method. The type of this research was descriptive. Data sources used were primary and secondary data. Data processing was done by editing method, then a qualitative analysis was performed by using the inductive-deductive method. The results showed that (1) the occurrence of homosexual crime on children was caused by factors of: social environment, pornography, and lack of family communication. (2) there were three opinions of fiqh scholars in determining criminal sanctions that can be imposed on homosexual offenders: the first opinion statesthat homosexual offenders shall be sentenced to death; the second opinionstipulates that homosexual offenders are sentenced as adultery. If he is a bikr (unmarried man) then his sentence is to be flogged and exiled from his country.While those who are muhsan (had been married), then he is punished by stoning. The thirdopinion stipulates that homosexual perpetrators must be given legal sanctions in the form ofta'zir, that is a kind of punishment which is aimed at educative and preventive in which theseverity is determined by the judge. This Islamic criminal sanctions are heavier than positivelaw, so they can create a deterrent effect, and reduce the number of sexual crimes on children.